A composite, off-the-shelf osteoinductive material for large, vascularized bone flap prefabrication. (December 2022) - Kouba, Loraine; Bürgin, Joël; Born, Gordian; Perale, Giuseppe; Schaefer, Dirk J.; Scherberich, Arnaud; Pigeot, Sébastien; Martin, Ivan
Abstract: We previously described an immortalized, genetically-engineered human M esenchymal stromal cell line to generate B MP2-enriched C hondrogenic M atrices (MB-CM), which after devitalization and storage could efficiently induce ectopic bone tissue by endochondral ossification. In order to increase the efficiency of MB-CM utilization towards engineering scaled-up bone structures, here we hypothesized that MB-CM can retain osteoinductive properties when combined with an osteoconductive material. We first tested different volumetric ratios of MB-CM:SmartBone® (as clinically used, osteoconductive reference material) and assessed the bone formation capacity of the resulting composites following ectopic mouse implantation. After 8 weeks, as little as 25% of MB-CM was sufficient to induce bone formation and fusion across SmartBone® granules, generating large interconnected bony structures. The same composite percentage was then further assessed in a scaled-up model, namely within an axially-vascularized, confined, ectopically prefabricated flap (0.8 cm 3 ) in rats. The material efficiently induced the formation of new bone (31% of the cross-sectional area after 8 weeks), including bone marrow and vascular elements, throughout the flap volume. Our findings outline a strategy for efficient use of MB-CM as part of a composite material, thereby reducing the amount required to fill large spaces and enabling utilization in critically sized grafts, to address challenging clinical scenarios in bone reconstruction. Statement of significance: Most bone repair strategies rely either on osteconductive properties of ceramics and devitalized bone, or osteoinductive properties of growth factors and extracellular matrices (ECM). Here we designed a composite material made of a clinically accepted osteoconductive material and an off-the-shelf tissue engineered human cartilage ECM with strong osteoinductive properties. We showed that low amount of osteoinductive ECM potentiated host cells recruitment to form large vascularized bone structures in two different animal models, one being a challenging prefabricated bone-flap model targeting challenging clinical bone repair. Overall, this study highlights the use of a promising human off-the-shelf material for accelerated healing towards clinical applications. Graphical abstract: Image, graphical abstract